Menurunkan Kerusakan yang Sering Terjadi pada Alat Berat Excavator Komatsu PC200-8 dengan Proses Perbaikan pada Sistem Bahan Bakar - Manurung, Vuko Arief Tua; Pamungkas, Danang Sigit; Wibowo, Yohanes Trijoko; Amir, Amir (Motor Bakar : Jurnal Teknik Mesin, 2023)
Maintenance of heavy equipment units is required to maintain and ensure the performance of the unit in ready-to-use condition. Damage that occurs, especially in the fuel system line, often causes the excavator unit to become low power, even when the engine turns off. In PT XYZ, damage of the fuel system often occurs causing the unit to undergo unscheduled breakdown. By using the fishbone method to find the cause of the problem, it was found that the existing treatments were not optimal so that problems that started to appear were not immediately followed up. By monitoring the maintenance schedule and accelerating the replacement of fuel filters, unscheduled repairs can be overcome and the physical availability target is achieved..